Self-assemblies of nucleolipid supramolecular synthons show unique self-sorting and cooperative assembling process - Nuthanakanti, Ashok; Walunj, Manisha B.; Torris, Arun; Badiger, Manohar V.; Srivatsan, Seergazhi G. (Nanoscale, 2019)
The inherent control of the self-sorting and co-assembling process that has evolved in multi-component biological systems is not easy to emulate in vitro using synthetic supramolecular synthons. Here, using the basic component of nucleic acids and lipids, we describe a simple platform to build hierarchical assemblies of two component systems, which show an interesting self-sorting and co-assembling behavior. The assembling systems are made of a combination of amphiphilic purine and pyrimidine ribonucleoside-fatty acid conjugates (nucleolipids), which were prepared by coupling fatty acid acyl chains of different lengths at the 2 `-O- and 3 `-O-positions of the ribose sugar. Individually, the purine and pyrimidine nucleolipids adopt a distinct morphology, which either supports or does not support the gelation process. Interestingly, due to the subtle difference in the order of formation and stability of individual assemblies, different mixtures of supramolecular synthons and complementary ribonucleosides exhibit a cooperative and disruptive self-sorting and co-assembling behavior. A systematic morphological analysis combined with single crystal X-ray crystallography, powder X-ray diffraction (PXRD), NMR, CD, rheological and 3D X-ray microtomography studies provided insights into the mechanism of the self-sorting and co-assembling process. Taken together, this approach has enabled the construction of assemblies with unique higher ordered architectures and gels with remarkably enhanced mechanical strength that cannot be derived from the respective single component systems.